Networked professional learning: relating the formal and the informal - Vaessen, Matthieu; Van Den Beemt, Antoine; De Laat, Maarten (Frontline Learning Research, 2014)
<!–[if gte mso 9]> u0059729 12.00 <![endif]–><span style="font-size: 11.0pt; font-family: ’Calibri’,’sans-serif’; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The increasing complexity of the workplace environment requires teachers and professionals in general to tap into their social networks, inside and outside circles of direct colleagues and collaborators, for finding appropriate knowledge and expertise. This collective process of sharing and constructing knowledge can be considered ’networked learning’. The processes involved are informal and largely invisible to the official framework of the organisation. Consequently, a large amount of learning that takes place is unrecognised and the dynamics, impacts and benefits of such networked learning are often overlooked by organisations. This situation brings about tensions between formal and informal processes, which in turn raises issues concerning management and adequate professional development. It also leads to questions about facilitating the creation and exchange of knowledge and expertise within the existing social networks. We examine the mechanisms for an optimal alignment and usage of teachers’ networked learning in the context of schools and professional development. Key questions this paper addresses are: What are the implications of learning through networks for professional development, autonomy, management and leadership? How can networked learning be promoted in the best way possible? Currently, a clear academic understanding in this area is lacking. Taking an interdisciplinary approach, we examine research in the areas of educational and organisational studies. Examining the underpinning values, we identify mechanisms related to learning networks. Our goal is to work towards a description of mechanisms that contribute to an alignment of informal and formal learning of teachers within their workplace: schools.<!–[if gte mso 9]> Normal 0 21 false false false NL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>